Pretest interview of polygraph expert and the subject as a basis for professional study of psycho-physiological examination using polygraph - Мотлях, Олександр Іванович; Тодосієнко, Анна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
It is recognized that the method of psychophysiological examination using a polygraph (here and after - PPEP) provides following steps of its implementation: pretest interview with the subject of conversation; direct testing of a person using polygraph and possible interview with the subject, his counsel (lawyer), or the initiators of this examination afterwards before the preparation and formalizing the expert’s conclusion. Each of the above steps are important, necessary and requires a competent expert polygraph approach to their preparation and implementation, as all this forms a process of implementation of PPEP. However, some polygraph experts argue that the most important in this particular process is the second and third stages of assessment, while understating the importance of pretest interviews with the subject. As for us, this position of polygraph researchers is inconsistent, even absurd, because their unique approach has elements of a short-sightedness and can almost negate the feasibility and effectiveness of psychophysiological examination of person’s imaginary memory traces using a polygraph, that need professional inspection and evaluation .